Goals, challenges and strategies for wound and bleeding management in total knee arthroplasty: A modified Delphi method. (12th November 2022) - Lyons, Matthew; Nunley, Ryan M; Ahmed Shokri, Amran; Doneley, Tyson; Han, Hyuk-Soo; Harato, Kengo; Kuwasawa, Ayano; Lee, Dae-Hee; Qi, Xin; Qian, Wenwei; Ratanachai, Siripong; Wang, Weijun; et al.
Background: Surgical techniques related to soft tissue management play critical roles in optimizing surgical outcomes and patient satisfaction in total knee arthroplasty (TKA). Despite the importance of wound closure and bleeding management approaches, no published guidelines/consensus are available. Methods: Twelve orthopedic surgeons participated in a modified Delphi panel consisting of 2 parts (each part comprising two rounds) from September–October 2018. Questionnaires were developed based on published evidence and guidelines on surgical techniques/materials. Questionnaires were administered via email (Round 1) or at a face-to-face meeting (subsequent rounds). Panelists ranked their agreement with each statement on a five-point Likert scale. Consensus was achieved if ≥70% of panelists selected 4/5, or 1/2. Statements not reaching consensus in Round 1 were discussed and repeated or modified in Round 2. Statements not reaching consensus in Round 2 were excluded from the final consensus framework. Results: Consensus was reached on 13 goals of wound management. Panelists agreed on 38 challenges and 71 strategies addressing surgical techniques or wound closure materials for each tissue layer, and management strategies for blood loss reduction or deep vein thrombosis prophylaxis in TKA. Statements on closure of capsular and skin layers, wound irrigation, dressings and drains required repeat voting or modification to reach consensus. Conclusion: Consensus from Asia-Pacific TKA experts highlights the importance of wound management in optimizing TKA outcomes. The consensus framework provides a basis for future research, guidance to reduce variability in patient outcomes, and can help inform recommendations for wound management in TKA.